2005
DOI: 10.1897/04-195r.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative thresholds for acetylcholinesterase inhibition and behavioral impairment in coho salmon exposed to chlorpyrifos

Abstract: Chlorpyrifos is a common organophosphate insecticide that has been widely detected in surface waters that provide habitat for Pacific salmon in the western United States. Although chlorpyrifos is known to inhibit acetylcholinesterase (AChE) in the brain and muscle of salmonids, the relationship between sublethal AChE inhibition and more integrative indicators of neuro-behavioral impairment are poorly understood. This is particularly true for exposures that reflect the typical range of pesticide concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
146
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(161 citation statements)
references
References 54 publications
(95 reference statements)
13
146
1
1
Order By: Relevance
“…Concentrations of individual contaminants and mixtures determined in this study have been shown to have adverse effects in a wide range of animals, including mammals, reptiles, amphibians, and fish (20)(21)(22)(23). Some of the effects described are as follows: alterations of growth and development (24), poor hatching success (22), alterations of the reproductive and nervous system (25,26), learning and behavioral deficits retained throughout life (27,28), abnormalities of the liver and other organ systems (29,30), and endocrine disruption (29,31). Studies have also shown that these contaminants in combination can increase adverse effects by several orders of magnitude (32,33).…”
Section: Discussionmentioning
confidence: 84%
“…Concentrations of individual contaminants and mixtures determined in this study have been shown to have adverse effects in a wide range of animals, including mammals, reptiles, amphibians, and fish (20)(21)(22)(23). Some of the effects described are as follows: alterations of growth and development (24), poor hatching success (22), alterations of the reproductive and nervous system (25,26), learning and behavioral deficits retained throughout life (27,28), abnormalities of the liver and other organ systems (29,30), and endocrine disruption (29,31). Studies have also shown that these contaminants in combination can increase adverse effects by several orders of magnitude (32,33).…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have linked effects of CPY on the sensory epithelium and behavior to inhibition of AChE. Working with juvenile Coho salmon ( Oncorhynchus kisutch ) exposed to CPY at concentrations between 0.6 and 2.5 μg L −1 , Sandahl et al ( 2005 ) showed that spontaneous swimming rate and food strikes were correlated (r 2 0.58 and 0.53, respectively) with inhibition of AChE activity in the brain. Other studies of effects of CPY in the same species showed that thresholds for different behaviors were related to inhibition of AChE (Tierney et al 2007 ).…”
Section: Sublethal Effects On Aquatic Animalsmentioning
confidence: 99%
“…Although herbicides could indirectly affect salmonids via effects to algae and plants, direct effects to fish from these pesticides are much less likely. In contrast to the other pesticide groups, carbamates and organophosphate pesticides are highly toxic to salmonids (Beauvais et al 2000(Beauvais et al , 2001Sandahl and Jenkins 2002;Sandahl et al 2005;Laetz et al 2009;NOAA 2009) and were frequently detected in the Washington State WRIAs from 2003 to 2007. Thus, carbamate and organophosphate pesticides are the pesticides of greatest concern for direct effects to Pacific salmonids.…”
Section: The Washington State Monitoring Studymentioning
confidence: 99%
“…Inhibition of AChE activity occurs in the central nervous system (CNS) and in the plasma and muscle of fish (Perkins and Schlenk 2000). Studies with a number of carbamate and organophosphate pesticides (e.g., azinphosmethyl, chlorpyrifos, malathion, diazinon, carbaryl) have demonstrated an association between inhibition of brain AChE activity and behavioral endpoints such as reduction in spontaneous swimming and feeding rates, swimming stamina, predator detection, and homing behavior (Post and Leasure 1974;Moore and Waring 1996;Van Dolah et al 1997;Beauvais et al 2000Beauvais et al , 2001Scholz et al 2000;Sandahl et al 2005;Labenia et al 2007).…”
Section: Toxicity Of Carbamates and Organophosphatesmentioning
confidence: 99%